Histopathologic predictors of recurrence and survival in early T stage oral tongue squamous cell carcinoma - Benjamin J. Damazo; Nihal A. Punjabi; Nihal A. Punjabi; Yuan F. Liu; Jared C. Inman (Frontiers Media S.A., 2024)
ObjectivesRecurrence and survival in early T-stage oral tongue squamous cell carcinoma (OTSCC) may be impacted by histopathologic risk factors. This study aims to examine which of these factors predict long-term outcomes of T1 and T2 OTSCC.MethodsA retrospective review of T1 and T2 OTSCC patients treated with surgery at a single tertiary care center was conducted. Multivariate regression and Kaplan-Meier survival plots were used to identify predictors of recurrence and compare disease-free survival respectively.Results100 consecutive patients were studied. Of these, 51 were staged pT1, 49 pT2, 69 pN0, 10 pN1, and 21 pN2. Multivariate regression analysis revealed that >4 nodes was the strongest predictor of overall recurrence [odds ratio 1.68 (1.23-2.28), p = 0.001], while >4 nodes [odds ratio 1.14 (1.09-1.85), p = 0.008] and pT2 [odds ratio 1.15 (1.01-1.30), p = 0.033] were predictors of local recurrence (R2 = 0.112). Five-year disease-free survival was not significantly impacted by any risk factors except for the number of positive nodes-86% for ≤4 nodes vs. 20% for >4 nodes (p < 0.001)-and pathologic T-stage-90% for pT1 vs. 75% for pT2 (p = 0.035) regardless of adjuvant radiation and/or chemotherapy use.ConclusionsPatients who underwent adjuvant radiation and/or chemotherapy had similar survival to those who did not despite having worse overall tumor prognostic factors. Adding adjuvant therapy may equalize some high-risk histopathologic factors. In the highest risk patients-specifically those with pathologic >4 nodes and pT2 staging-adjuvant therapy should be considered.